13C‐gastric emptying breath tests: Clinical use in adults and children. Issue 6 (17th May 2021) - Keller, Jutta; Hammer, Heinz F; Hauser, Bruno
Abstract: 13 C‐gastric emptying breath tests ( 13 C‐GEBT) are validated, reliable, and non‐invasive tools for measurement of gastric emptying (GE) velocity of solids and liquids without radiation exposure or risk of toxicity. They are recommended and routinely used for clinical purposes in adult as well as pediatric patients and can be readily performed onsite or even at the patient's home. However, the underlying methodology is rather complex and test results can be influenced by dietary factors, physical activity, concurrent diseases, and medication. Moreover, epidemiological factors can influence gastric emptying as well as production and exhalation of 13 CO2, which is the ultimate metabolic product measured for all 13 C‐breath tests. Accordingly, in this issue of Neurogastroenterology & Motility, Kovacic et al. report performance of the 13 C ‐ Spirulina breath test in a large group of healthy children and show significant effects of gender, pubertal status, and body size on test results. The purpose of this mini‐review is to evaluate the clinical use of 13 C‐GEBT in adults and children, exploring available protocols, analytical methods, and essential prerequisites for test performance, as well as the role of GE measurements in the light of the current discussion on relevance of delayed GE for symptom generation.